2018
DOI: 10.1111/jav.01660
|View full text |Cite
|
Sign up to set email alerts
|

Grazing pressure affects offspring sex ratio in a socially monogamous passerine on the Tibet Plateau

Abstract: Livestock grazing can affect habitat structure and availability of arthropod prey for grassland birds, and ultimately determines habitat quality. The habitat quality may affect breeding strategies (e.g. sex ratio adjustment) in bird species, but studies investigating grazing intensity on offspring sex ratio are still rare. In this paper, we examined the effect of grazing intensity by livestock on the secondary sex ratio of an alpine‐steppe passerine, the isabelline wheatear Oenanthe isabellina, on the Tibet Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The average annual temperature recorded in this area was −1.0 • C with a total annual rainfall of 350 mm based on data collected from 1990 to 2010. Around 30 bird species nest in this area, and further details on the research site are available in Li et al [29].…”
Section: Study Site and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average annual temperature recorded in this area was −1.0 • C with a total annual rainfall of 350 mm based on data collected from 1990 to 2010. Around 30 bird species nest in this area, and further details on the research site are available in Li et al [29].…”
Section: Study Site and Methodsmentioning
confidence: 99%
“…The confounding effect-number of yearly broods, which is hard to control for species in low-land studies, can be easily reduced at high altitudes. Besides, the habitat at high altitudes tends to be more homogenous [29][30][31], while diverse habitat at low land might confound the final results. Species of different low-land regions experiences rather different biotic and abiotic environment (e.g., climate, vegetation and predator density) which might confound the final results [14].…”
Section: Introductionmentioning
confidence: 99%
“…When a nest was located, we recorded the date and nest status (presence of parents, eggs, nestlings) with nests then checked every 2–4 days. Open‐cup nests were checked directly while cavity nests were checked either by a pole‐mounted miniature camera or through a hole dug at the side of the nest chamber (previous studies showed no obvious adverse effects from these methods; Li, Shi, et al., 2018 ). For cavity nests, we recorded the entrance location (on ground or on cliff bank) and measured the burrow length from entrance to the burrow chamber with a measuring tape to 0.1 cm.…”
Section: Methods and Study Sitementioning
confidence: 99%
“…Mammals (e.g., Siberian Weasel M. sibirica and Wild Cat Felis silvestris) are predominant predators in our study site Li S's unpublished data). Details on the study site are available in Li, Shi, et al (2018). Current study (Continues) during the incubation or nestling periods.…”
Section: Study Sitementioning
confidence: 99%
“…An embryo (id alw_001) of this species was sampled in an unhatched egg from an abandoned nest, on June 21th 2017 at bush habitat of Tianjun County (37°18′N, 99° 01′E; 3416 m altitude), northeastern of Tibet Plateau (details of the habitat are available in Li et al. 2018 ). The sample was immediately stored in alcohol.…”
mentioning
confidence: 99%